ADVANCED ENGLISH LANGUAGE STUDY USING DELIBERATIVE TECHNIQUE IN THE ENGLISH AS A FOREIGN LANGUAGE CLASSROOM - Evi Nopiyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2012)
This article discusses the perspective of modern and the latest up date of teaching technique through deliberative methodology which means consultative. In this case, deliberative focuses on how to employ speech communication, discussion on debate, drama on role play, simulation and presentation. Those has something to do with speaking ability, I can say mostly spoken takes big part in developing language master. Here, I emphasize that this approach is more available to be applied for students who has capability in speaking. In the other hand, students who are poor in speaking will be able to speak fluently as long as they have good motivation, confidence and knowledge about problem discussed. Furthermore, the deliberative technique approach looks more systematic so that teachers can do the teaching steps based on the cronology concept or planning teaching map.Key Word: Speech, presentation, debate, role play, simulation.